Plastic debris characteristics and the effect of wind on Bawean Island Beaches, East Java, Indonesia - Nurhafizh Sri Albarra; Defri Yona; Muhammad Arif Asadi; Syarifah Hikmah Julinda Sari; Riski Agung Lestariadi; Akhmad Amirudin (Depik Jurnal)
Characteristics of plastic debris were assessed among two types of beaches on Bawean Island (windward and leeward) to analyze its sources and long-term effects. Plastic debris was collected inside a 5 x 5 meter transect with five transect plots on each beach per 20 meters. Samplings were carried out three times at intervals of seven days from six different beaches. The average abundances of plastic debris were almost similar between leeward (0.169±0.123 pcs m